2010
DOI: 10.1080/10934520903538707
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba leaf extract action in scavenging free radicals and reducing mutagenicity and toxicity of cigarette smokein vivo

Abstract: In this study, ginkgo biloba leaf extract (GBE) was added to sample cigarettes, including in the filter (0.8 mg/cigarette) and/or the cut filler (0.8 mg/cigarette). The effects of GBE in scavenging free radicals and reducing mutagenicity and toxicity of cigarette smoke in vivo were investigated. Smoke analysis results indicated that GBE eliminated up to 30% of free radicals. Biological experiments, conducted for both GBE cigarettes and control samples, included the Ames test, acute toxicity, neutral red cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Therefore, ECSOD exerts critical protective effects against oxidative stress-induced PF (30). Previous studies have suggested that the predominant active ingredients in GBLE are flavonoids (31)(32)(33). These flavonoids have the ability to dilate blood vessels, improve microcirculation, resist oxidation, scavenge oxygen free radicals and prevent or reverse the fibrosis of multiple organs, thus alleviating PF and reducing the degree of alveolitis and fibrosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ECSOD exerts critical protective effects against oxidative stress-induced PF (30). Previous studies have suggested that the predominant active ingredients in GBLE are flavonoids (31)(32)(33). These flavonoids have the ability to dilate blood vessels, improve microcirculation, resist oxidation, scavenge oxygen free radicals and prevent or reverse the fibrosis of multiple organs, thus alleviating PF and reducing the degree of alveolitis and fibrosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the predominant active ingredients in GBLE are flavonoids (31)(32)(33). These flavonoids have the ability to dilate blood vessels, improve microcirculation, resist oxidation, scavenge oxygen free radicals and prevent or reverse the fibrosis of multiple organs, thus alleviating PF and reducing the degree of alveolitis and fibrosis (33,34). Ginseng saponin and Ophiopogonin D are the primary active ingredients in S, which may inhibit the activation of myofibroblasts by scavenging free radicals and blocking the free-radical-generation enzyme system, thus acting as antioxidants and reducing PF (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Both modified versions of cigarettes had less toxicity and mutagenicity than non‐modified cigarette and the animals, which were exposed to GB‐contained cigarette experienced milder toxicity‐related complications, so it means that GB lowered the toxic effects of cigarette smoke. On the other hand, there were much lower amounts of solid and gas‐phase free radicals related to modified version in comparison with non‐modified one (Wang et al, ; Wang et al, ). Therefore, the protective effects of GB might originate from its radical scavenging and antioxidant activity.…”
Section: Chemical Toxicitiesmentioning
confidence: 99%
“…In two separated assays of Wang et al ( and 2011), GBLE was utilized alone and with cobalt porphyrin in cigarette filter to minimize the toxicity of its smoke. After preparing the GB‐contained cigarettes, a system was applied to produce and trap the cigarette smoke in order to test its free radical contents, in vivo acute and chronic toxicity in the animals.…”
Section: Chemical Toxicitiesmentioning
confidence: 99%
“…G. biloba extract (GbE), isolated from the dried leaves of G. biloba, has been reported to have many beneficial activities, including free radical scavenging (Wang et al, 2010), antioxidative (Boghdady, 2013), anti-inflammatory (Chen et al, 2013b), anti-tumor activities (Tsai et al, 2014), and neuroprotective effects (Abd-Elhady et al, 2013). GbE has become one of the best-selling botanical supplements in many European countries and in the USA for the prevention and adjunctive treatment of vascular and cognitive diseases, such as Alzheimer's disease (Oken et al, 1998;Tchantchou et al, 2007), vertigo (Hamann, 2007;Sokolova et al, 2014), tinnitus (Hilton et al, 2013;Tziridis et al, 2014), and peripheral arterial occlusive diseases (Unger, 2013;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%